Mapping out marketing : navigation lessons from the ivory trenches - Hill, Ronald Paul; Lamberton, Cait, 1975-; Swartz, Jennifer, 1988- (Routledge, 2018)
"Sea-changes in society, technology, consumer expectations and our understanding of behavioral economics have caused us to rethink our understanding of the scope of knowledge required to navigate, analyze and shape consumer behavior. You hold in your hand a field guide for this adventure. Ron Hill and Cait Lamberton have gathered together the very top professors from around the world and invited them to share the beliefs, practices and wisdom that they have developed and honed across years and contexts. Each of these luminaries shares personal stories and deep insights about the way that not only business works, but the way we, ourselves, navigate the world. These short contributions are contained in eight "destinations" that showcase overlapping and essential topics, ranging from technology to subsistence marketplaces, followed by unique questions that are answered by the material provided. The research described has helped the field understand the central role of exchange in marketing relationships, and how product features, pricing strategies, delivery mechanism and various communication modalities create or fail to produce functioning marketplaces around the world. In addition, it reminds us all of the need to continue to learn, to grow, and to share our knowledge in whatever corner of the marketing world we find ourselves."--Provided by publisher.